2020
DOI: 10.2147/dddt.s251005
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nano-Graphene Oxide-supported APTES-Spermine, as Gene Delivery System, for Transfection of pEGFP-p53 into Breast Cancer Cell Lines</p>

Abstract: Purpose Genetic diseases can be the result of genetic dysfunctions that happen due to some inhibitory and/or environmental risk factors, which are mostly called mutations. One of the most promising treatments for these diseases is correcting the faulty gene. Gene delivery systems are an important issue in improving the gene therapy efficiency. Therefore, the main purpose of this study was modifying graphene oxide nanoparticles by spermine in order to optimize the gene delivery system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…On the other hand, the wide range of lateral sizes is advantageous to meet different requirements for biological applications [ 49 , 50 ]. GO nanoparticles ranging from 50 to 200 nm have consistently been demonstrated in multiple investigations to bypass immune cells, diffuse through vessel walls and the ECM, and infiltrate breast cancer cells effectively [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Characteristics Of Go As a Nanocarriermentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the wide range of lateral sizes is advantageous to meet different requirements for biological applications [ 49 , 50 ]. GO nanoparticles ranging from 50 to 200 nm have consistently been demonstrated in multiple investigations to bypass immune cells, diffuse through vessel walls and the ECM, and infiltrate breast cancer cells effectively [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Characteristics Of Go As a Nanocarriermentioning
confidence: 99%
“…These results indicated that depending on the application, fabricating a carrier that can diffuse the mentioned barriers to reach the targeted site of the body raises the demand for achieving a uniform size of GO particles using the mentioned approaches. In addition, different sizes of functionalized GO have been utilized for breast cancer therapy [ 17 , 51 , 53 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Characteristics Of Go As a Nanocarriermentioning
confidence: 99%
See 3 more Smart Citations